Franklin Collinear Antenna 2 Levels Different Sides using Array Method 4 Stacking Units 360ᵒ with Integrated Reflector and Power Combiner for ADS-B S-Receiver Mode - Yussi Perdana Saputera; Topik Teguh Estu; Teguh Praludi; Ganis Sanhaji (National Research and Innovation Agency, 2021)
In this study, an antenna system that could cover the 360ᵒ detection area using the microstrip method was created. The antenna design proposed uses the franklin collinear method with the addition of an array of arms to the left and right of the antenna and the addition of reflectors as a gain enhancer. The four antenna array units are combined using a power divider (combiner) as a unifying antenna. Antenna design with end fire radiation pattern cannot be used in receiving the ADS-B antenna system, because it works only in certain sectors with certain beamwidth, so it needs to be modified by adding an array of 4 units that make up 360◦ radiation of directional diagrams. The addition of the reflector is done by testing the optimum width. The most optimum width is obtained by the width of the side addition on the side of the antenna aperture cross section width of 80 mm. Based on the results of experiments that have been carried out for the design of receiver antennas for ADS-B applications that are required in the form of a radiation pattern in all directions using the reflector technique, the most appropriate gain increase is to use a phase difference for the antennas that are closest both left and right by 90o in ¼ λ conditions in the integration process using a 4 way power combiner. Response return loss at frequency 1.0752 GHz and 1.109 GHz is -15 dB, it means antenna has 33.8 MHz bandwidth with maximum response return loss at -23.22 dB and gain of 7.586 dBi, this antenna design is very suitable for use in the ADS-B application. Design and simulation at this antenna used CST software.